Post-harvest Storage of Guava (Psidium guajava, L, var. Taiwan) - Augustin, M. A.; Osman, Azizah (1988)
Guava fruit (var. Taiwan) were stored at room temperature (26°C), 200e and 50 e and the characteristics of the fruits during storage were evaluated. Guava fruit has a post-harvest life of about 1 week during room temperature storage and post-harvest life can be extended by a few days during storage at 20°C. At 2~ eand 200 e, post-harvest life is limited by the occurrence of rots. At~e, bronzing of the guava skin occurs at about 2 weeks of storage. Rots were not evident during storage at 5°e. The average pH, total soluble solids and titratable acidity of guava at harvest was 3.5,5.4°Brix and 62.8 ml O.lNaOH/ 100g respectively. The levels of individual soluble sugars were: fructose 1.60 g/100g, glucose 1.06g/1 OOg and sucrose O. 78g/1 OOg at the commencement of the study. There were significant increases in total soluble solids during storage at all temperatures. Titratable acidity did not change significantly during storage for 10 days at room temperature and 200 e and during storage for 4 weeks at 5° e. There were significant increases in fructose, glucose and total soluble sugars but no significant differences in sucrose levels during storage at room temperature. Significant increase in fructose levels and total soluble sugar levels were also obtained during storage at 200 e and 5°e. The fructose/glucose ratios significantly increased during storage at all temperatures.